A reliability optimization allocation method for the hydraulic system of CNC honing machine considering the operating condition information. (June 2018) - Zhou, Guanghui; Chang, Fengtian; Tian, Changle; Lu, Qi
In recent years, reliability optimization allocation has drawn a broad spectrum of attentions, especially for complex systems consisting of a large number of subsystems and components. Hydraulic system, deemed as a complex system, plays a great role in reliability increment of the CNC honing machine. In order to realize the CNC honing machine tool's balanced operating performance, the crucial hydraulic system is designed to obtain the optimal and well-balanced allocation solution under the constrains of cost and reliability. Meanwhile, the quantified operating factor that influences the allocation solution is rarely considered adequately when operating samples are insufficient. So, if hydraulic systems are used in a new required longer operating mission duration or a new severer operating environment, the dissatisfied reliability could not be better reallocated to adapt to this environment with appropriate methods. Aimed at overcoming the abovementioned shortcomings and optimizing the dissatisfied reliability for existing hydraulic systems, this paper proposes a reliability optimization allocation method considering operating the condition information. From the standpoint of the complex system, this method firstly builds a three-level reliability optimization allocation model based on the analytic target cascading for the specific hydraulic system of CNC honing machine 2MK2263 × 200. It transforms the complex reliability allocation problem to a set of smaller and coordinated optimization sub-problems. Secondly, through studying the operating reliability problems of small samples in the new operating scene, the reliability prediction results based on the operating condition information are applied to build the initial reliability targets, which are regarded as the initial constrains for the optimization. With the help of analytic target cascading model and initial target reliability, the optimal reliability for the complex hydraulic system would be obtained. It is also shown to provide an innovative route for the reliability redesign of the related complex systems for this new required operating scene.